From shame to sin : the Christian transformation of sexual morality in late antiquity - Harper, Kyle, 1979- (Cambridge, Massachusetts : Harvard University Press, 2013)
The transformation of the Roman world from polytheistic to Christian is one of the most sweeping ideological changes of premodern history. At the center was sex. Kyle Harper examines how Christianity changed the ethics of sexual behavior from shame to sin, and shows how the roots of modern sexuality are grounded in an ancient religious revolution.
Introduction: From city to cosmos -- The moralities of sex in the Roman Empire -- The will and the world in early Christian sexuality -- Church, society, and sex in the age of triumph -- Revolutionizing romance in the late classical world -- Epilogue: Sex and the twilight of antiquity.
Includes bibliographical references and index.
Print version record.
In English.
Master record variable field(s) change: 650
Keywords: Sex -- History -- To 1500.; Sexual ethics -- History -- To 1500.; Sex -- Religious aspects -- Christianity; Civilization, Classical; Rome -- Moral conditions; PSYCHOLOGY -- Human Sexuality; SELF-HELP -- Sexual Instruction; RELIGION -- Sexuality & Gender Studies; Civilization, Classical; Moral conditions; Sex; Sex -- Religious aspects -- Christianity; Sexual ethics; Rome (Empire); Ancient History; Classical Studies; Sex -- History -- To 1500.; Sex -- Religious aspects -- Christianity; Sexual ethics -- History -- To 1500.; To 1500; Electronic books; History